The brain-friendly workplace : why talented people quit and how to get them to stay - Fabritius, Friederike (Rowman & Littlefield, 2022)
"A smart, science-based approach to retaining your talent and making the world of work a better place. Today's work isn't working. Stress and burnout are driving talented professionals out of the workforce while the corporate standard of extreme hours, sleep deprivation, and nonstop travel proves unsustainable. But innovative leaders are using this once-in-a-century opportunity to create a future of work that's better for everyone. The workplace of tomorrow is a hybrid ecosystem that thrives on flexibility and diversity of thought, enabling all employees to reach peak performance. Every person's brain is different and by taking an inclusive view towards neurosignature diversity, organizations can get a competitive advantage. In The Brain-Friendly Workplace, Friederike Fabritius offers a science-based and field-tested blueprint for tomorrow's workplace. Leaders capable of enacting change or individuals searching for ways to work smarter will discover that even small and inexpensive changes can lead to advantages like better employee performance, higher job satisfaction, and stronger talent retention. If you have been longing for a better way of working where you and your people are both happy and productive, The Brain-Friendly Workplace can make that vision a reality"--